3D-printed Sr2ZnSi2O7 scaffold facilitates vascularized bone regeneration through macrophage immunomodulation - Pan, Hao; Deng, Li; Huang, Lingwei; Zhang, Qi; Yu, Jing; Huang, Yueyue; Chen, Lei; Chang, Jiang (Frontiers in Bioengineering and Biotechnology, 2022)
Biomaterial-based bone grafts are emerged as an effective strategy for the treatment of large bone defects, especially for the scaffolds with enhanced osteogenic and angiogenic bioactivities. However, most studies focused on the direct interactions between scaffolds and bone-related cells such as osteoblasts and endothelial cells, and ignored the effects of material-triggered immunomodulation and the subsequent immune-regulated bone regeneration process. In this study, we developed a silicate bioceramic (Sr2ZnSi2O7, SZS) scaffold with well-defined pore structures using a three-dimensional (3D) printing technique. The prepared scaffolds were biodegradable, and the released bioactive ions were beneficial for immunomodulation, which stimulated macrophages to release more pro-healing cytokines and less pro-inflammatory cytokines. The obtained scaffold/macrophage conditioned medium further promoted the proliferation and osteogenic differentiation of a murine preosteoblast cell line (MC3T3-E1), as well as the angiogenic activity of human umbilical vein endothelial cells (HUVECs). Moreover, the in vivo experiments of critical-sized calvarial defects in rats revealed that the 3D printed SZS scaffolds could facilitate more vascularized bone regeneration than the 3D printed β-tricalcium phosphate (β-TCP, a typical clinically used bioceramic) scaffolds, suggesting that the 3D-printed SZS scaffolds hold the potential as implantable biomaterials with favorable osteoimmunomodulation for bone repair.